2014
DOI: 10.1038/jid.2014.124
|View full text |Cite
|
Sign up to set email alerts
|

The Desmosomal Protein Desmoglein 1 Aids Recovery of Epidermal Differentiation after Acute UV Light Exposure

Abstract: Epidermal structure is damaged by exposure to ultraviolet (UV) light but the molecular mechanisms governing structural repair are largely unknown. UVB (290-320 nm wavelengths) exposure prior to induction of differentiation reduced expression of differentiation-associated proteins, including Desmoglein 1 (Dsg1), Desmocollin 1 (Dsc1) and Keratins 1 and 10 (K1/K10) in a dose-dependent manner in normal human epidermal keratinocytes (NHEKs). The UVB- induced reduction in both Dsg1 transcript and protein was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 57 publications
(73 reference statements)
5
42
0
Order By: Relevance
“…These desmosomal components are also downregulated in human keratinocytes derived from AEC patients and focal downregulation of DSP and DSC3 expression is observed in non-lesional skin of AEC patients (Ferone et al 2013;Koster et al 2014), confirming their possible causative role in the pathogenesis of AEC syndrome. In agreement with a dominant negative function of AEC mutation, Dsp, Dsc3 and Dsg1 are also downregulated in p63-depleted keratinocytes and are shown to be direct p63 target genes by luciferase (Luc) assay and ChIP experiments (Ferone et al 2013;Johnson et al 2014). A dramatic reduction in Dsg1 expression was similarly reported in ΔNp63 GFP/GFP mice (Romano et al 2012), while Dsp and Dsc3 were not tested.…”
Section: P63 and Desmosomessupporting
confidence: 53%
“…These desmosomal components are also downregulated in human keratinocytes derived from AEC patients and focal downregulation of DSP and DSC3 expression is observed in non-lesional skin of AEC patients (Ferone et al 2013;Koster et al 2014), confirming their possible causative role in the pathogenesis of AEC syndrome. In agreement with a dominant negative function of AEC mutation, Dsp, Dsc3 and Dsg1 are also downregulated in p63-depleted keratinocytes and are shown to be direct p63 target genes by luciferase (Luc) assay and ChIP experiments (Ferone et al 2013;Johnson et al 2014). A dramatic reduction in Dsg1 expression was similarly reported in ΔNp63 GFP/GFP mice (Romano et al 2012), while Dsp and Dsc3 were not tested.…”
Section: P63 and Desmosomessupporting
confidence: 53%
“…It has long been known that PKC signaling regulates expression of desmosomal cadherins in keratinocytes (Denning et al 1998). Suppression of PKC-a or PKC-d isoforms increases Dsg3 expression, whereas suppression of PKC-d and PKC-1 isoforms either decreases or increases Dsg1 levels, respectively (Szegedi et al 2009 (Roemer 2012) and p63 has been shown by chromatin immunoprecipitation (ChIP) to bind and activate Dsg1, Dsc3, and Dp promoters (Ferone et al 2013;Johnson et al 2014). Rho-mediated changes in the actin cytoskeleton lead to changes in Srf-dependent transcription (Miralles et al 2003) and Srf controls the expression of Pkp2 and Dsg1, which in turn drives a program of terminal differentiation (Leitner et al 2011;Dubash et al 2013), The Wnt-regulated TCF/Lef transcription complex has been implicated in regulation of Dsg4, Dsc2, Dsc3, and Pg expression but direct binding of these transcription factors to desmosomal component promoters has only been shown in a few instances (Table 1) (Bazzi et al 2009;Bailey et al 2012;Tokonzaba et al 2013).…”
Section: Transcriptional Regulation Of Desmosomal Componentsmentioning
confidence: 99%
“…In line with these findings, Dsg1 and Dsc1 are reduced by UVB (290-to 320-nm wavelengths) exposure in keratinocytes beginning to differentiate. Importantly, ectopic Dsg1 expression counteracts UVB-induced loss of differentiation markers (Johnson et al 2014) indicating that desmosomal components contribute directly to epidermal responses to carcinogenic exposure.…”
Section: Desmosomes and The Epidermal Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years identified a number of transcriptional factors that modulate 4 O. HUBER & I. PETERSEN desmosomal cadherin expression including Stat6, Klf5, Smad4, grainy head-like 1, Foxn1, Cdx1/Cdx2, c-Rel, lymphocyte enhancer factor/transcription factor (LEF/ TCF), and p53/p63 (Ferone et al, 2013;Funakoshi et al, 2008;Johnson et al, 2014;Kenchegowda et al, 2012;Mlacki et al, 2014;Omori-Miyake et al, 2014;Oshiro et al, 2003;Owens et al, 2008;Tokonzaba et al, 2013;Wilanowski et al, 2008). Interestingly, plakoglobin in a complex with LEF-1 is able to bind to the proximal promoter regions of both Dsc2 and Dsc3, however with opposite effects.…”
Section: Transcriptional Regulation Of Desmosomal Cadherinsmentioning
confidence: 99%